(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: The exploration of “self” in literature currently faces a significant methodological gap. It is well-established that using cognitive linguistic theory is more rigorous than abstract philosophical negotiations of the “self”. Since cognitive linguistic theories grant an understanding of types of communication and cognitive processes, stylisticians are trying to benefit from useful frameworks from this interdisciplinary field to analyze literary texts. This study aims to demonstrate how Cognitive Linguistic theory can handle and give a comprehensive image to “split-self” phenomena found in narrative texts referring to Chika Unigwe’s On Black Sister’s Street. Specifically, the researchers investigate how characters’ selves oscillate between polar modes of self in a narrative which in turn reflects the sense of fragmentation of identity in postcolonial society. They draw on Lakoff’s (1992, 1996) works on the ‘self’ metaphor and the division of subject-self. The analysis reveals that the author projects the traumatic experiences of characters through using split-self metaphors which proves the utility of Cognitive Linguistics in providing important techniques that assist in understanding latent themes in literary texts. Keywords:cognitive linguistics, split- self metaphor, subject, self. ملخص: يواجه استكشاف "الذات" في الأدب حاليًا فجوة منهجية كبيرة. من الثابت أن استخدام نظرية اللسانيات المعرفية يعد أكثر صرامة من المفاوضات الفلسفية المجردة حول "الذات". نظرا لأن اللسانيات المعرفية تمنح فهمًا لأنواع الاتصالات والعمليات المعرفية، يحاول باحثو الأسلوبية الاستفادة من أطر مفيدة من هذا المجال متعدد التخصصات لتحليل النصوص الأدبية. تهدف هذه الدراسة إلى توضيح كيف يمكن لنظرية اللسانيات المعرفية التعامل وإعطاء صورة شاملة لظاهرة "الانقسام الذاتي" الموجودة في النصوص السردية مشيرة إلى رواية لما بعد الاستعمار: "شارع الأخوات السود" لشيكا يونيجوي. على وجه التحديد، يتحرى الباحثون كيف تتأرجح ذوات الشخصيات بين الأنماط القطبية للذات في السرد الذي يعكس بدوره الإحساس بتجزئة الهوية في مجتمع ما بعد الاستعمار. سنستند إلى أعمال لاكوف (1992 ، 1996) على استعارة "الذات" وتقسيم الذات. يكشف التحليل أن المؤلف يعرض التجارب المؤلمة للشخصيات من خلال استخدام الاستعارات المنقسمة على الذات والتي تثبت فائدة اللسانيات المعرفية في توفير تقنيات مهمة تساعد في فهم الموضوعات الكامنة في النصوص الأدبية. كلمات دالة : اللسانيات المعرفية، استعارة انقسام الذات، الموضوع، الذات.